The impact of ICT usage, workplace organisation and human capital on the provision of apprenticeship training. a firm-level analysis based on Swiss panel data - Heinz Hollenstein; Tobias Stucki (ETH Zurich, KOF Swiss Economic Institute, 2008)
Firstly, we investigated the determinants of a) the propensity of Swiss firms to provide apprenticeship training, and b) the intensity of training (measured by the employment share of apprentices). We primarily were interested in the relevance as explanatory factors of the three constituent elements of the new firm paradigm that emerged in the course of the last twenty years: intensive usage of ICT; redesign of workplace organisation; shift from lower to higher skills. We found that the skill composition of the workforce (including further training), ICT intensity and, to a lesser extent, workplace organisation are important drivers of apprenticeshipbased skill formation, with stronger effects on training propensity than on training intensity. Secondly, we analysed the relationship between apprenticeship training and firm performance. It turned out that productivity and apprenticeships (training propensity or intensity) are negatively correlated. The study is relevant for training policy in advanced economies where the new firm paradigm plays a large and growing role.
Keywords: J2; L2; O3; M5; 330; Firm-based training; Apprenticeship; Workplace organisation; ICT; Skill formation; Human capital; Betriebliche Ausbildung; Arbeitsgestaltung; Qualifikation; Informationstechnik; Humankapital; Schweiz